Merrifield-Simmons Index in Random Phenylene Chains and Random Hexagon Chains - Ailian Chen (Discrete Dynamics in Nature and Society)
The author obtains explicit expressions for the expected value of the Merrifield-Simmons index of a random phenylene chain and a random hexagon chain, respectively. The author also computes the corresponding entropy constants and obtains the maximum and minimum values in both random systems, respectively.